PENERAPAN MODEL PROBLEM BASED LEARNING BERBASIS BERDIFERENSIASI UNTUK MENINGKATKAN HASIL BELAJAR IPS - Serly Octavia Privana; RR. Nanik Setyowati; Masnidar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the extent to which the social studies learning outcomes of class IX J students at SMP Negeri 22 Surabaya have improved through the application of a differentiated approach using the Problem Based Learning model. This research method uses Classroom Action Research (PTK) involving literary steps from planning, implementation, observation and reflection on learning actions. The research participants consisted of 33 class IX J students who were actively involved in the posttest learning process. Data analysis was carried out by looking at the classical average value and classical completeness value. The research results show that the application of a differentiated approach using the Problem Based Learning model improves students' social studies learning outcomes. This is proven by the classical completeness level of 40%, namely from 12% to 52% with details of 17 out of 33 students having completed it compared to during the first cycle, namely only 4 students who had reached the completion mark. These findings provide an important contribution to educational practice, especially in designing more interactive and student-centered learning strategies to improve their learning outcomes in social studies subjects.